ROMANIAN AUTOMOTIVE SECTOR AMID COVID-19 PANDEMIC CRISIS: IMPACT ON PRODUCTION AND PRODUCTIVITY - Maria Daniela BONDOC (Publishing house of University of Pitesti, Romania, 2020)
For more than eight months, the global economy has been challenged to cope with an unprecedented health crisis affecting both individuals and businesses. The pandemic generated by the COVID-19 virus has rapidly spread globally and continues to strongly threaten the entire economy. After tourism, the automotive sector suffers the most. The analysis proposed in this paper aims at comparisons between the level of some economic indicators in the Romanian automotive sector (production, average number of directly productive staff, productivity) in 2020 and 2019 to highlight the impact of the state of emergency and then the state of alert established at national level due to the COVID-19 pandemic. The car market has been hit hard by the crisis of this pandemic, and there has been a sharp decline in production and sales. The automotive industry is one of the key components of the global economy, and the downturn has affected and will severely affect society as a whole.